Analytical Assessment of Internal Stress in Cemented Paste Backfill. (22nd December 2020) - Liu, Naifei; Cui, Liang; Wang, Yan
Abstract : To analytically describe the internal stress in a fill mass made of granular man-made material (cemented paste backfill, CPB), a new 3D effective stress model is developed. The developed model integrates Bishop effective stress principle, water retention relationship, and arching effect. All model parameters are determined from measurable experimental data. The uncertainties of the model parameters are examined by sensitivity analysis. A series of model application is conducted to investigate the effects of field conditions on the internal stress in CPB. The obtained results show that the proposed model is able to capture the influence of operation time, stope geometry, and rock/CPB interface properties on the effective stress in CPB. Hence, the developed model can be used as a useful tool for the optimal design of CPB structure.